Anemia at Diagnosis in Pediatric Solid Tumors: Prevalence, Severity, and Hematologic Patterns: A Single-center Retrospective Study - PM, Swathi; Macharla, Aparna; S., Nishanth; MV, Archana; Rahiman, Emine A.; Belurkar, Sushma; Koulmane Laxminarayana, Sindhura; Bhat K, Vasudeva (Indian Journal of Medical and Paediatric Oncology, 2025)
Anemia is a frequent clinical finding at the time of diagnosis in children with solid tumors and may reflect tumor biology, nutritional status, or bone marrow involvement. However, the pattern and severity of anemia across different solid tumor types in children remain underreported.The aim of this study was to evaluate the prevalence and characteristics of anemia at presentation among pediatric patients with various solid tumors.This retrospective observational study included 149 children with newly diagnosed solid tumors, aged 0 to 18 years. Anemia was classified based on the World Health Organization age-specific hemoglobin thresholds and further categorized into mild, moderate, and severe grades. Tumors were classified into bone tumors, central nervous system (CNS) tumors, abdominal tumors, soft tissue sarcomas, germ cell tumors, and others. Associations between anemia and tumor type were analyzed using descriptive statistics and chi-square tests.Anemia was present in 67 (45%) patients at diagnosis. Bone tumors detected in 52 patients (34.9%) and CNS tumors detected in 34 patients (22.8%) were the most common malignancies. Among those with anemia, 36.4% had mild, 45.5% moderate, and 18.2% severe anemia. Statistical analysis revealed a significant association between red cell indices (mean corpuscular volume, mean corpuscular hemoglobin [MCH], red cell distribution width [RDW], mean corpuscular hemoglobin concentration) and anemia status (p < 0.001), with low MCH and high RDW suggesting the anemia was predominantly microcytic and hypochromic, with substantial anisocytosis.Anemia is a common presenting feature in pediatric solid tumors. Detailed investigations to delineate the etiology of anemia are necessary to guide targeted management of the tumor as well as to correct the anemia.
Keywords: anemia; prevalence; red cell indices; pediatric